2020
DOI: 10.1021/acsami.9b22537
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence-Sensing Tb-MOF Nanozyme for the Detection and Degradation of Estrogen Endocrine Disruptors

Abstract: Using flexible structures and components of metal-organic framework (MOF) materials, we designed and developed an artificial nanozyme with dual functions of a catalyst and luminescent sensor specifically for the determination and degradation of hormone 17β-estradiol (E2) and its derivatives (E1, E3, and EE2), a class of disruptors with strong effect on the human endocrine system. This nanozyme composed of the luminescent Tb3+ ion, catalytic coenzyme factor hemin, and light-harvesting ligand can be used to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…The presence of 4,4′‐oxybisbenzoic acid and hemin in Tb‐MOF provided a good environment for electrostatic interactions between CO and the peroxide hydrogen atom in a complex system. [ 189 ] Furthermore, the introduction of nanoparticles into MOFs changed the sensing behavior for H 2 O 2 detection to the quenching effect. [ 190 ] Notably, MOFs bearing the same metal center but different linker functionalities showed different sensing behaviors.…”
Section: Mofs Sensing Behavior Toward Toxic Chemicalsmentioning
confidence: 99%
“…The presence of 4,4′‐oxybisbenzoic acid and hemin in Tb‐MOF provided a good environment for electrostatic interactions between CO and the peroxide hydrogen atom in a complex system. [ 189 ] Furthermore, the introduction of nanoparticles into MOFs changed the sensing behavior for H 2 O 2 detection to the quenching effect. [ 190 ] Notably, MOFs bearing the same metal center but different linker functionalities showed different sensing behaviors.…”
Section: Mofs Sensing Behavior Toward Toxic Chemicalsmentioning
confidence: 99%
“…Estrogens are known as endocrine-disruptor compounds (EDCs) widely spread in the aquatic system and other environments. Indeed, the attendance-and endocrine-disrupting potency of these molecules in waters, soil, and food are 10,000 times higher than common synthetic chemicals, for example pesticides [1][2][3]. Estrone (E1), 17β-estradiol (E2), 17β-ethinylestradiol (EE2), and estriol (E3) are the most extended estrogens in the environment and their origin can be various (human urine and feces, cattle activities, aquaculture, among others) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal-organic frameworks (MOFs) compounds composed of metal-oxygen clusters bridged by organic linking molecules are becoming a new class of enzyme mimics [32]. The porous 3D coordination polymers have larger specific surface areas and a higher density of accessible catalytic sites [33], which makes it possible to be a type of excellent peroxidase mimicking materials [34][35][36]. It has been reported that MOFs constructed by Zr6 and porphyrin possess framework hyperstability for the strong electrostatic interactions between high valence Zr IV and carboxylate linkers [37,38].…”
Section: Introductionmentioning
confidence: 99%